2018
DOI: 10.1111/1755-5922.12463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of evidence‐based cardiac drug therapy on mortality in patients with acute coronary syndrome: Findings from the Gulf COAST registry

Abstract: Among patients discharged after an ACS event, concurrent EBM prescribing was associated with lower all-cause mortality that persists for up to 12-months posthospital discharge. The relative benefits of EBMs were also consistent across age, GRACE risk score, and discharge diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
4
8
0
Order By: Relevance
“…In addition, a greater probability to achieve the LDL-C target was observed in male patients and in the elderly, as already known (29).…”
Section: Discussionsupporting
confidence: 62%
“…In addition, a greater probability to achieve the LDL-C target was observed in male patients and in the elderly, as already known (29).…”
Section: Discussionsupporting
confidence: 62%
“…The details of the assessment are presented in Table 1. The eight cohort studies assessed by the NOS checklist, three studies had eight stars [42], [43], [44] and the remaining four studies had nine stars [45], [46], [47], [48], [49], representing high quality. The details of the assessment are shown in Table 2.…”
Section: Study Qualitymentioning
confidence: 99%
“…Statin utilization at admission ranged from 11.43% to 94.8%. Unfortunately, there were only two studies whose statin utilization at admission was more than 50% [6], [47]. In terms of statin utilization during hospitalization, many studies (7 out of 11 studies) reported that statin utilization was higher than 80% [22], [29], [30], [32], [34], [51], [52].…”
Section: Statin Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kuwait, there has been an increased interest in the management of patients with CVD and the provision of evidence-based clinical services by practitioners in recent years ( Zubaid et al, 2020 ; Al-Zakwani et al, 2018 ; Longenecker et al, 2013 ). However, there is a lack of the literature assessing prescribing practices in the management of CVDs by health-care providers.…”
Section: Introductionmentioning
confidence: 99%